Re/Un/Discover: An embodied heuristic for uncertainties in social work practice - Keenan, Elizabeth King (Australian Social Work, 2021)
Social workers have always worked with and within uncertainties in practice, but the COVID-19 pandemic is amplifying the frequency and degree of uncertainty across ecological levels. Social workers need enhanced capacity to work with these uncertainties and the impact on individual and collective wellbeing. The RE/UN/DIScover heuristic guides social workers’ responses to the wide range of practice uncertainties experienced in the moment and over time. Drawing on understandings of embodied wellbeing from interpersonal neurobiology and the power relations manifest in intersectional positionality, RE/UN/DIScover offers embodied, iterative practices to access the wealth of capabilities within self and others. IMPLICATIONS Disruptions and uncertainties connected with pandemics, economic recessions, continued systemic injustices and other human-made problems can challenge social workers and impact the wellbeing of individuals and communities. Heuristics are guides that sort, order, and inform decisions and actions. The RE/UN/DIScover heuristic uses knowledge about embodied wellbeing and various forms of power to guide social workers. RE/UN/DIScover offers social workers practices to use with uncertainties both in the moment and over time. © 2020 Australian Association of Social Workers.
Keywords: dept.swk; peer-reviewed

RE/UN/DIScover Heuristic: Working with Clinical Practice Impingements in Dehumanizing Times - Keenan, Elizabeth King (Clinical Social Work Journal, 2023)
Although clinical social work seeks to center the transformative potential of human relationships, practitioners are experiencing heightened systemic and organizational impingements from the dehumanizing pressures of neoliberalism. Neoliberalism and racism diminish the vitality and transformative potential of human relationships, disproportionately affecting Black, Indigenous and People of Color (BIPOC) communities. Practitioners are also experiencing increased stress and burnout related to increased caseloads and decreased professional autonomy and organizational practitioner support. Holistic, culturally responsive, and anti-oppressive processes seek to counter these oppressive forces but need further development to synthesize antioppressive structural understandings with embodied relational interactions. Practitioners can potentially contribute to efforts that apply critical theories and antioppressive understandings within their practice and workplace. Through an iterative flow of three sets of practices, the RE/UN/DIScover heuristic supports practitioners’ efforts to respond in those challenging everyday moments where oppressive forms of power are imposed and embedded within systemic processes. With themselves and other colleagues, practitioners engage in compassionate REcover practices; use curious, critical reflection to UNcover full understandings of power dynamics, impacts, and meanings; and draw on creative courage to DIScover and enact socially just and humanizing responses. This paper describes how practitioners can use the RE/UN/DIScover heuristic in two common challenging moments of clinical practice: systemic practice impingements and implementing a new training or practice model. The heuristic seeks to support practitioners’ efforts to preserve and expand socially just, relational spaces for themselves and those with whom they work within the context of systemic dehumanizing neoliberal forces.
Keywords: Clinical practice; Heuristic; Neoliberalism; Power; Practice challenges; Window of tolerance; dept.swk; peer-reviewed

Deepening the learning: Intersectional experiential activities to address white supremacy - Keenan, Elizabeth King; Kozu, Shuei; Mayhew, Hunter; Saiter-Meyers, Evelyn; Meggett, Caliyah; Reynolds, Paige (Advances in Social Work, 2021)
Graduate students of multiple racial identities in predominantly White institutions enter social work programs with a wide range of knowledge about and experiences of White Supremacy, particularly the ways in which structural forms of racism continue to inflict harm, block opportunities, and perpetuate wealth inequities. In addition, White students are often challenged to grasp the ways they have been socialized to participate in perpetuating White Supremacy. This wide range of knowledge and experiences makes it likely that students will experience a range of emotions and defensive resistance necessitating skillful pedagogical design and facilitation of class interactions. Intentional use of theoretical frameworks with experiential activities can deepen self-awareness and understanding of the systemic nature of White Supremacy (Okun, 2010). In this manuscript, four students and two instructors discuss their learning experiences within a course addressing White Supremacy for students of multiple racial identities in a predominantly White institution. Post-course dialogue amongst these multiracial authors identified six core areas of learning when examining intrapersonal, interpersonal, and structural racism, cultural wealth of BIPOC peoples, and anti-racism actions. Two primary implications for education are: Weave conceptual frameworks with interpersonal experiential activities throughout the course design, and attend to interactional power dynamics during class meetings. © 2021 Authors, Vol. 21 No. 2/3 (Summer 2021), 821-840,.
Keywords: dept.swk; peer-reviewed

If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
Keywords: White supremacy; dept.swk; peer-reviewed